2015
DOI: 10.1515/jas-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Ovary Development in Honeybee (Apis Mellifera L.) Workers Under Co2 Narcosis, Caged Outside of the Colony

Abstract: A b s t r a c t Exposure of A. mellifera workers to CO 2 has been reported to decrease life span, induce behavioral changes, and inhibit the development of some glands and the ovaries. However, the use of CO 2 is currently practiced among beekeepers and how the development of workers' ovaries are affected is unknown. The present work aimed to evaluate the effect of CO 2 on the ovaries of A. mellifera workers, using a morphological approach. Newly emerged, and 3, 5, and 10-day-old workers were exposed to satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Understanding these mechanisms can also clarify why the impacts of CO 2 are caste dependent in both bumble bees (current study) and honey bees (15, 25, 59). If CO 2 activates network of genes related to hormones and vitellogenesis that have decoupled during the evolution of social behavior (6062), then the downstream effects on worker and queen reproduction are easier to explain.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Understanding these mechanisms can also clarify why the impacts of CO 2 are caste dependent in both bumble bees (current study) and honey bees (15, 25, 59). If CO 2 activates network of genes related to hormones and vitellogenesis that have decoupled during the evolution of social behavior (6062), then the downstream effects on worker and queen reproduction are easier to explain.…”
Section: Discussionmentioning
confidence: 89%
“…CO2 narcosis has pleiotropic impacts on insect physiology and behavior. These effects have been documented in multiple orders including Orthoptera (8), Diptera (9,10), Hemiptera (11), and Hymenoptera (12)(13)(14)(15). CO2 narcosis in Drosophila melanogaster resulted in changes in fecundity and longevity (10) and reduced climbing behavior (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 narcosis is known to inhibit ovary activation in A. mellifera workers (Harris et al 1996;Koywiwattrakul et al 2005;Berger et al 2015) but how it does so is unclear. Thus we were interested to see if narcosis would change methylation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Given the conditions for colony organization, three types of controls can influence queen ovarian function: an intrinsic control due to genetics and physiology; a colony environment control derived from interactions between castes and colony conditions, such as colony age demography, the number of cells available for egg laying and available food; and the beekeeper's management practice, such as fumigation that exposes bees to CO 2 that has an effect on the ovary of workers and queens (Berger and Cruz-Landim 2012;Berger et al 2015;Butler and Simpson 1965;CruzLandim et al 2006;Hamilton 1964;Hartfelder 2000;Page and Ericksons 1988;Patrício and Cruz-Landim 2003). Although Cobey (2007) found that the colony environment is indispensable for the start of oogenesis in the ovaries, the results herein showed that even in queens maintained outside of the colony environment, follicle differentiation can advance until separation of the oocyte and pre-nurse cells, which is just one step short of the ovarian development seen in queens maintained inside a colony.…”
Section: Discussionmentioning
confidence: 99%